Synthesis of Zeolite from Fly Ash and Removal of Heavy Metal Ions from Newly Synthesized Zeolite - Parag Solanki; Vikal Gupta; Ruchi Kulshrestha (E-Journal of Chemistry)
Coal fly ash was used to synthesize X-type zeolite by alkali fusion followed by hydrothermal treatment. Characteristics of the various Fly ash samples were carried out. Coal proximate analysis was done. Batch experiment was carried out for the adsorption of some heavy metal ions on to synthesized Zeolite. The cost of synthesized zeolite was estimated to be almost one-fifth of that of commercial 13X zeolite available in the market.